Hubungan Kadar Matrix Metalloproteinase-9 pada Cairan Serebrospinal dan Serum terhadap Derajat Keparahan dan Luaran Pasien Meningitis Tuberkulosis - Sonia Hardianti; Yuliarni Syafrita; Fanny Adhy Putri; Syarif Indra; Restu Susanti; Reno Bestari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Tuberculous meningitis (TBM) is a severe form of tuberculosis associated with high mortality and neurological morbidity. Disease severity strongly influences outcome; however, reliable biological predictors remain limited. Matrix metalloproteinase-9 (MMP-9) is a proteolytic enzyme involved in neuroinflammation and blood-brain barrier disruption, and it has been reported to be elevated in both the cerebrospinal fluid (CSF) and serum of TBM patients. This study aimed to evaluate the relationship between MMP-9 levels and the severity and outcome of TBM patients. This was an analytical observational study with a cross-sectional design involving TBM patients treated at Dr. M. Djamil General Hospital, Padang, from January to December 2024. CSF and serum MMP-9 levels were measured using the enzyme-linked immunosorbent assay (ELISA) method. Disease severity was assessed using the British Medical Research Council (BMRC) criteria, and outcomes at 14 and 60 days were assessed using the Glasgow Outcome Scale. A total of 41 TBM patients were included in the study. The mean CSF MMP-9 level was 2,034.40 ng/L, while the median serum MMP-9 level was 1,490.14 ng/L. The analysis showed no significant association between CSF MMP-9 levels and disease severity (p = 0.276), 14-day outcome (p = 0.269), or 60-day outcome (p = 0.375). Serum MMP-9 levels were likewise not associated with disease severity (p = 0.248), 14-day outcome (p = 0.224), or 60-day outcome (p = 0.138), but they still showed an increasing pattern in patients with a fatal outcome. CSF and serum MMP-9 levels had no significant association with the severity and outcome of TBM patients. These findings suggest that a single MMP-9 measurement is insufficient as a clinical predictor, so a multibiomarker and longitudinal approach should be considered.